Peningkatan Hasil Belajar Pokok Bahasan Pencemaran Lingkungan Mata Pelajaran IPA Dengan Metode The Learning Cell Siswa Kelas VII D SMP Negeri 1 Balla Kabupaten Mamasa - Elisaberth Rambulangi; Mithen Lullulangi (Seminar Nasional LP2M UNM, 2021)
Abstrak. This study aims to improve learning outcomes of science subjects on the subject of Environmental Pollution, VII D grade students of SMP Negeri 1 Balla, using The Learning Cell method. This type of research is an experimental inquiry research which is realized in the form of Classroom Action Assessment (CAR). The data collection method used is observation of the learning process, and at the end of each learning process, a test is carried out to determine the success of the learning process. Analysis technique is descriptive qualitative with plot method. The flow that is passed in qualitative data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that: The use of The Learning Cell learning method on the subject of Environmental Pollution in science subjects for class VII D SMP Negeri 1 Balla, there was an increase in student activity and learning outcomes gradually, seen in terms of: participation, interest, and ability as well as an increase the learning outcomes, which are shown in the learning outcomes of the first cycle which are still far from expectations, (only 26%) are completed, but have increased in the second cycle by 84% which are completed and the remaining 16% are not completed. Kata Kunci: Improvement, Learning Outcomes, The Learning Cell